Uncovering Employee Engagement in the Power of Leadership, Communication, and Teamwork Study: Mengungkap Keterlibatan Karyawan dalam Studi Kekuatan Kepemimpinan, Komunikasi, dan Kerja Sama Tim - Indah Wulandari; Vera Firdaus (Academia Open, 2024)
This study investigates the impact of servant leadership, communication, and teamwork on employee engagement at PT Irawan Djaja Agung, aiming to address a gap in research regarding their combined influence in Indonesian organizations. Through a quantitative survey of 70 employees and analysis using Smart-PLS Version 3.0, the research finds significant positive relationships between servant leadership, communication, teamwork, and employee engagement. The results highlight the importance of nurturing supportive leadership, enhancing communication channels, and fostering teamwork to bolster employee engagement. Organizational leaders are urged to consider implementing recognition and reward systems, while employees are encouraged to strengthen interpersonal relationships for improved collaboration. Further research could delve into additional factors affecting employee engagement in similar contexts. Highlight: Synergy of Leadership, Communication, Teamwork. Quantitative Analysis with Smart-PLS. Actionable Insights for Organizational Improvement. Keyword: Servant leadership, Communication, Teamwork, Employee engagement, Organizational development